THE IMPACT OF SUPPLIER RELATIONSHIPS ON BORN GLOBAL FIRMS` INTERNATIONALIZATION - Fehèr, Àgnes (My University, 2014)
Purpose: Building on the resource-based perspective and the network theory of the firm, this thesis explores how supplier relationships facilitate the internationalization of born global firms. The study examines what kind of relationships born globals develop with their suppliers and how those specific relationships contribute to the firms` operation and internationalization. The causes of past and possible future changes in supplier relationships are also discussed. The study makes a comparison between born globals being in their start-up stage and born globals being in their growth stage of their life cycle. Design/methodology/approach: The thesis uses deductive approach while its research design is the combination of descriptive and exploratory studies. The empirical research applies qualitative methodology using semi-structured interviews. Findings: The result shows that strategic manufacturing suppliers providing specialized components and final assembly have significant importance in the firms` operation. Next to improving efficiency and increasing the born global`s knowledge-base, they contribute to the firm`s internationalization through production globalization and production offshoring. Research limitations/implications: The international scope of the study is considerably limited to a single country, Finland and even to a single region inside the country. Furthermore, the research focuses on a specific industry; that is the energy technology industry. As for the implications, the study shows that suppliers do have a direct role in the firm`s internationalization which should not be ignored. Originality/value: The research contributes to the born global literature by studying its downstream supplier relationships which got limited attention by academics to date.
Keywords: Born globals; Supplier relationship; Strategic alliances; Competitive advantage; Internationalization; fi=Master's Degree Programme in International Business|; fi=Organisaatioiden viestintä|en=Communication in organizations|